2023
DOI: 10.1109/access.2023.3271408
|View full text |Cite
|
Sign up to set email alerts
|

An Attention-Based Convolutional Neural Network for Intrusion Detection Model

Abstract: Network technology has had a distinctive impact on the entire human civilization and has become an important factor of production in many countries and regions. However, with the widespread popularity of network technology, security flaws have been scattered in various fields, and potential crises may break out by attackers at any time. Therefore, it is crucial to establish a traffic monitoring mechanism for network systems. Some researchers have already implemented intrusion detection models by convolutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…CNN-based IDS techniques are categorized using a brand-new system. The study found that the hybrid auto-encoder with CNN achieved 84.39% accuracy on the NSL-KDD dataset [8,9]. Furthermore, Al-Turaiki et al's research [10] presents a novel anomaly-based network intrusion detection method.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…CNN-based IDS techniques are categorized using a brand-new system. The study found that the hybrid auto-encoder with CNN achieved 84.39% accuracy on the NSL-KDD dataset [8,9]. Furthermore, Al-Turaiki et al's research [10] presents a novel anomaly-based network intrusion detection method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Binary features (7,12,14,20,21,22) describe attributes with two states, while categorical features (2, 3, 4, 42) reflect qualitative variables with distinct categories. Discrete features (8,9,15,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)43) are unique numeric variables, but continuous features (1,5,6,10,11,13,16,17,18,19) can take any real value within a range. The dataset's 'attack' label has 40 labels, categorizing attacks as revised, U2R, DoS, R2L, and probing.…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from their experiments indicate that their models are accurate and recall well, outperforming similar models in the literature. A CNN intrusion detection model based on attention is proposed in the study 17 . The combination of the image generation methods presented in this paper results in a processing flow that is efficient and accurate.…”
Section: Related Workmentioning
confidence: 99%
“…Each feature is represented as a binary matrix in the form of a 4 × 4 matrix. In total, 64 features are selected (arranged 8 × 8), which will be represented by a 32 × 32 matrix 17 .…”
Section: Proposed Schemementioning
confidence: 99%